A Methods engineering study of Nissan Motor Philippines, Inc. - Borja, June U.; Manza, Pinky Maricris P.; Rendon, Elza D.; Sarip-Macmud, Zaida (College of Engineering, 1994)
Nissan Motor Philippine, Incorporated (NMPI) is an automobile manufacturing company located at 222 E. Rodriguez Sr. Boulevard, Quezon City, Philippines. It was established in October 1982 as a joint venture among Nissan Motors Company, Ltd., Marubeni, Sta Cruz Corporation, and Auto-Equities, Inc. NMPI aims to manufacture high quality vehicles that would suit the customers' taste and satisfaction. At present its product line is composed of Sentra, Vanette, Bluebird Altima Bida, and Sunny Pick-up. The production of these vehicles involves three (3) main processes : car body or 'shell' assembly which is done at the Body Shop, painting processes and car erection wherein the car machine and all other car parts are installed. This present operation has its certain degree of efficiency. This efficiency can be improved further. This is what the study aims to accomplish. The study focused on the Body Shop Jig section because of several constraints and restricting factors, e.g. time limit. The Jig Dedicated line is where the 'shells' of Sentra are assembled with welding as the main process involved. The line is subdivided into twelve (12) stations on which thirteen (13) workers work. To be able to arrive at certain ways to improve efficiency, data are gathered through observation and interviews. From this gathered facts and data, the group conducting the study were able to identify the areas that need management attention and concern. These problem areas are: 1. work sequence; 2. work environment; 3. work space and layout; 4. safety measures. Work sequence can be further improved. Ideally, per station or per job requires one worker except for station 10 or Body Main. However, the time the study is conducted this is not the case. Some worker has more than one job. And most of them try to do these jobs simultaneously which require them to travel from jig to jig or sometimes from station to station. This frequent walking lengthen time of operation and causes machine idle time. Also work environment and condition is not satisfactory i.e. temperature of workplace is above normal and the noise level is high. This causes difficulty of concentration among workers, high error rates and fatigue increases thus efficiency decreases. The space is small and limited and there is overcrowding of material (assembled and to be process) racks in stations. The machine and equipments however, do not occupy much space for they are connected to above fixture. Lay-out also needs redesigning. Since assembly process is cumulative i.e. an assembled part in one station is to be connected to the part assembled in another station, the work following one another must be close to each other to avoid delays in transporting the needed materials. However this is not the present case. As for safety measures, workers are given aprons, helmet/caps, spectacles, gloves and other means of protection from untoward incidents. But some workers do not use these. Upon analyzing these problem area the following alternative solutions are generated : 1. concerning the work sequence, if it is not possible for the management to assign at least one worker per job, a worker must not shift from one work to another especially when his works are far apart. He must choose which work needed to be done first e.g. if Station 2 is to connect the assembled part from Station 1 but none is available the station one must assemble that part first to avoid idle time in Station 2. 2. The work environment and condition can be improved by installing ventilation to counteract above normal temperature and with regard to noise the use of ear plugs can be implemented. 3. The workplace can not be further enlarged but can be maximize through proper placement of material racks. Fixed racks may be installed and use other rack for transport. This may lessen overcrowding due to improper placement of racks provided the racks for transport has been put to its designated area when not in use. 4. Strict safety rules must be implemented. And managers, supervisors, and foremen must see to it that these rules are being followed. These alternatives when use may result in increased efficiency thus objective is met. Therefore all these may be considered as solutions. Also these alternatives are quite simple and easy to implement and need not cost much. The use of charts and diagrams were utilized. This facilitate study analysis. Work measurement is also included in the study. Direct time study is the technique used. Only one station in the jig dedicated line is timed because of the constraints stated earlier. This station is the Partial Shelf. The time study resulted in the identification of ineffective time i.e. the time in which no effective work is done. Example of these is unnecessary talks with his co-worker while working. The ineffective time must be given certain attention by the management. The computed standard time 6.325.